Penerapan Prinsip Desain Grafis dalam Kampanye Digital Melawan Judi Online Melalui Animasi 2D - Rahadian Ngabanga; Feliza Zubair; Rinda Aunillah Sirait (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The increasing prevalence of online gambling, particularly among teenagers and young adults, serves as the background for the creation of the 2D animated work titled “Digital Threat: The Dangers of Online Gambling”.This project aims to educate and raise awareness about the negative impact of gambling financial, psychological, and social. The produkction process was carried out through several stages, including pre-production (idea development, scriptwriting, and storyboarding), production (creation of visual assets using tools such as the shape tool and pen tool, with layered elements prepared for animation). The final output is a short animated video that tells the story of a main character who becomes entangled in online gambling but eventually realizes the consequences and seeks help. The animation emphasizes clear, informative visual using the poppins font and a combination of original and legally sourced assets from platforms such as Freepik. In conclusion, this work and well documented. it is hoped that the animation can serve as a campaign and educational tool to support efforts in combating online gambling in Indonesia.